Influence of non-thermal maturity factors on laser Raman spectroscopy of highly to overmature shale: a case study of Lower Paleozoic marine shale in southern Sichuan Basin - Hongfei ZHANG; Kun JIAO; Jiayu WANG; Ning XU; Lijun MA; Lanfeng LIU; Yunjun WU; Bin DENG; Juan WU; Yuehao YE; Quanzhong GUAN; Xiangxin WANGZHOU; et al. (Shiyou shiyan dizhi, 2025)
Laser Raman spectroscopy has become increasingly prevalent in assessing the thermal maturity of ancient marine shale due to its advantages of simple sample preparation, easy operation, and non-destructive analysis. Current studies primarily focus on the response of Raman spectral parameters to thermal maturity variations, while research on the influence of non-thermal maturity factors, such as spectrum processing methods, sample pretreatment, and laser wavelength settings, on experimental accuracy remains relatively scarce and inconsistent. Using laser Raman spectroscopy, this study conducted a systematic comparative analysis of highly to overmature black shale samples from the Upper Ordovician Wufeng Formation and Lower Silurian Longmaxi Formation and Lower Cambrian Qiongzhusi Formation in the Sichuan Basin, with a particular focus on the impact of non-thermal maturity factors on parameters such as Raman band separation (RBS), full width at half maximum (FWHM), and the intensity ratio of D peak to G peak (ID/IG). The findings are as follows: (1) Spectrum processing methods: Two-peak fitting demonstrated lower uncertainty and higher efficiency than five-peak fitting, making it more suitable for thermal maturity assessment of highly to overmature shale, especially for the processing of Raman spectra of shale in Qiongzhusi Formation. (2) Parameter selection: Positional parameters (WD, WG, and RBS) showed thermal maturity differences of less than 2% after peak fitting, indicating high stability. Conversely, among the peak shape parameters (ID/IG, FWHM-D, FWHM-G), ID/IG was less affected by peak fitting and demonstrated better sample discrimination. Therefore, RBS and ID/IG are recommended as priority parameters in thermal maturity correlation studies. (3) Sample pretreatment: Polishing treatment has an overall impact of less than 3% on the Raman parameters of highly to overmature black shale from the Wufeng Formation and Longmaxi Formation. However, to accurately locate the dispersed organic matter within the black shale, polishing prior to Raman analysis is recommended.